Ezrin expression in female reproductive tissues: A review of regulation and pathophysiological implications - Xu, Wen-Ting; Shi, Ling-Li; Xu, Jie; Qian, Haiqing; Zhou, Huifang; Wang, Li-Hong (Frontiers in Cell and Developmental Biology, 2023)
Ezrin, a plasma membrane-microfilament linker, is a cytoskeletal organizer involved in many cellular activities by binding to the membrane protein-ezrin-cytoskeletal protein complex and regulating downstream signal transduction. Increasing evidence demonstrates that ezrin plays an important role in regulating cell polarity, proliferation and invasion. In this study, we analyzed the effects of ezrin on oocytes, follicle development, embryo development and embryo implantation. We reviewed the recent studies on the modalities of ezrin regulation and its involvement in the biological processes of female reproductive physiology and summarized the current research advances in ezrin inhibitors. These studies will provide new strategies and insights for the treatment of diseases.